Recent Publication Trends in Radiotherapy and Male Infertility over Two Decades: A Scientometric Analysis - Roychoudhury, Shubhadeep; Das, Anandan; Panner Selvam, Manesh Kumar; Chakraborty, Saptaparna; Slama, Petr; Sikka, Suresh C.; Kesari, Kavindra Kumar (Frontiers in Cell and Developmental Biology, 2022)
Radiotherapy, a popular cancer management procedure, negatively impacts reproductive health particularly by reducing the fertility potential. The purpose of this study was to analyze the research trend in radiotherapy associated with male infertility over the past 20 years (2000-May 2021). SCOPUS database was used to retrieve relevant scientometric data (publication per year, affiliation, journals, countries, type of document and area of research) for different subgenres of radiotherapy and male infertility. A total of 275 articles were published related to radiotherapy and male infertility, with the United States being the most dominant country in research output in this field. Radiotherapy and male infertility research have shown positive growth over the last two decades. In-depth analysis revealed that publications (n) related to radiotherapy and male infertility research mainly focused its impact on semen parameters (n = 155) and fertility preservation techniques (n = 169). Our scientometric results highlight a limited research focus on the field of radiotherapy and its impact on male reproductive hormones. Furthermore, a significant lack of research was noticed in the area of omics and male reproductive organs linked to radiotherapy. Substantial research is warranted to further decipher the effect of radiotherapy, at molecular level, leading to male infertility.